2013
DOI: 10.1111/jeb.12187
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in reproduction and growth among 52 range‐wide populations of aMediterranean conifer: adaptive responses to environmental stress

Abstract: A plastic response towards enhanced reproduction is expected in stressful environments, but it is assumed to trade off against vegetative growth and efficiency in the use of available resources deployed in reproduction [reproductive efficiency (RE)]. Evidence supporting this expectation is scarce for plants, particularly for long-lived species. Forest trees such as Mediterranean pines provide ideal models to study the adaptive value of allocation to reproduction vs. vegetative growth given their among-populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 66 publications
(92 reference statements)
9
100
1
Order By: Relevance
“…(2009) suggested precocious reproduction as a mechanism of compensation for the disadvantages. Although the reproductive size thresholds of long‐lived plants has been studied in several studies (Barot et al., 2005; Davies & Ashton, 1999; Santos‐del‐Blanco et al., 2013; Thomas, 1996; Wright et al., 2005), Bruijning et al. (2017) are the only one to examine the association between the sex expression of plants and their size at the onset of flowering.…”
Section: Discussionmentioning
confidence: 99%
“…(2009) suggested precocious reproduction as a mechanism of compensation for the disadvantages. Although the reproductive size thresholds of long‐lived plants has been studied in several studies (Barot et al., 2005; Davies & Ashton, 1999; Santos‐del‐Blanco et al., 2013; Thomas, 1996; Wright et al., 2005), Bruijning et al. (2017) are the only one to examine the association between the sex expression of plants and their size at the onset of flowering.…”
Section: Discussionmentioning
confidence: 99%
“…As found in previous studies, areas with milder temperatures and higher rainfall selected for high growth rates, non-conservative water use efficiency and low reproductive investment (Ferrio et al 2003;Voltas et al 2008Voltas et al , 2015Santos-del-Blanco et al 2013). This could be explained by selective pressures favouring a competitive strategy, involving more investment in vegetative growth in order to outcompete neighbouring trees (Grime 1977;Falster and Westoby 2003).…”
Section: Phenotypic Variation Environmental Correlations and Trade-offsmentioning
confidence: 72%
“…Previous studies had already found intraspecific genetic variability in the species for growth traits (Voltas et al 2008;Esteban et al 2010;Santos-del-Blanco et al 2013;De La Mata et al 2014), water use efficiency (Ferrio et al 2003;Chambel et al 2007;Voltas et al 2008Voltas et al , 2015 and morphometric and anatomical traits (Esteban et al 2010). We did not find Table 2.2).…”
Section: Phenotypic Variation Environmental Correlations and Trade-offsmentioning
confidence: 99%
See 2 more Smart Citations